Al- Qāmūs aš-šāmil li-muṣṭalaḥāt al-ʿulūm al-iǧtimāʿīya wa-'l-insānīya Inǧilīzī, ʿArabī = Comprehensive dictionary of terms social sciences - Maṭar, Ḥāzim Muḥammad Ibrāhīm; Saiyid, Ǧumāna Muḥammad Ramaḍān (Dār al-Ḥāmid lin-Našr wa-'t-Tauzīʿ, 2015)
Social sciences; humanities; dictionaries